Effects of Heart Cryoextract on Myocardial Antioxidant Capacity in Rats With Adrenaline-Induced Acute Myocardial Dystrophy - Chyzh, Mykola O; Matvieienko, Mariia; Hladkykh, Fedir V; Liadova Тetiana I; Komorovsky, Roman R; Karafulidi, Olha V (Scripta Medica, 2025)
Background/Aim. In a healthy heart reactive oxygen species (ROS) are by-products of normal metabolism and perform important signalling functions (sometimes referred to as “redox signalling” or oxidative eustress). Aim of this study was to investigate the cardioprotective mechanisms of porcine heart cryoextract, specifically its effect on the regulation of antioxidant defence in cardiomyocytes in an adrenaline‐induced myocardial dystrophy model. Methods. Eighty‐four male rats were divided into four groups: intact control (I), myocardial dystrophy without treatment (II), dystrophy + cryoextract (III) (50 μg peptides per 100 g body weight daily for 14 days) and dystrophy + amiodarone (IV) (10 mg/kg daily for 14 days). Myocardial dystrophy was induced by subcutaneous injection of 0.18 % adrenaline solution (5 mg/kg). On days 2, 7 and 14, superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx) activities and reduced glutathione (G-SH) content were measured in plasma and cardiac tissue using spectrophotometric and fluorometric assays. Results. On day 2, myocardial dystrophy caused significant decreases in SOD activity (–69.2 %), catalase (–54.4 %), GPx (–40.1 %) and G-SH content (–46.7 %) compared to intact controls (p < 0.001). Cryoextract treatment promoted early restoration of SOD activity (up to 54.6 %), catalase (up to +30.8 %), GPx (+6.7 %) and G-SH (+37.5 %) by day 2 (p < 0.01). By day 14, the cryoextract group’s enzyme activities and G-SH levels approached those of intact animals and exceeded the effect of amiodarone on GPx and G-SH (p < 0.05). Conclusions. Porcine heart cryoextract exerts a pronounced cardioprotective effect in an adrenaline‐induced myocardial dystrophy model by restoring the activity of key endogenous antioxidant enzymes and reduced glutathione levels. It surpasses amiodarone in the speed and extent of GPx and G-SH normalisation, supporting its further investigation as a biotherapeutic agent for correcting oxidative stress in cardiomyopathies.